There are 3. They're 16,25 and 36
Step-by-step explanation:
x=y+9
substitute
3(y+9)+8y=-6
3y+27+8y= -6
13y = -6 -27
13y= -33
y = -33/13
x = -33/13 + 9
Answer:
![\dfrac{-8}{\pi}](https://tex.z-dn.net/?f=%5Cdfrac%7B-8%7D%7B%5Cpi%7D)
Step-by-step explanation:
The rate of change of the function f(x) from point
to point
can be calculated using formula
![\dfrac{f(x_2)-f(x_1)}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cdfrac%7Bf%28x_2%29-f%28x_1%29%7D%7Bx_2-x_1%7D)
Given
![x_1=\pi\\ \\x_2=2\pi](https://tex.z-dn.net/?f=x_1%3D%5Cpi%5C%5C%20%5C%5Cx_2%3D2%5Cpi)
From the graph of the function
![f(x_1)=f(\pi)=4\\ \\f(x_2)=f(2\pi)=-4](https://tex.z-dn.net/?f=f%28x_1%29%3Df%28%5Cpi%29%3D4%5C%5C%20%5C%5Cf%28x_2%29%3Df%282%5Cpi%29%3D-4)
So, the rate of change is
![\dfrac{f(x_2)-f(x_1)}{x_2-x_1}=\dfrac{-4-4}{2\pi -\pi}=\dfrac{-8}{\pi}](https://tex.z-dn.net/?f=%5Cdfrac%7Bf%28x_2%29-f%28x_1%29%7D%7Bx_2-x_1%7D%3D%5Cdfrac%7B-4-4%7D%7B2%5Cpi%20-%5Cpi%7D%3D%5Cdfrac%7B-8%7D%7B%5Cpi%7D)
4 - (0) = y
4 - 0 = 4 y = 4
4 - (1) = y
4 - 1 = 3 y = 3
4 - (2) = y
4 - 2 = 2 y = 2
4 - (3) = y
4 - 3 = 1 y = 1
The break-even point is given when:
![C(x)=R(x)](https://tex.z-dn.net/?f=C%28x%29%3DR%28x%29)
In another words, when the costs are equal to the revenue. If this happens, the profit will be equal to 0. From the graph, the profit is equal to 0 for 60,000 units.
Answer:
B